2005
DOI: 10.1142/s0219843605000442
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating With Humanoid Robots in Space

Abstract: One of the great challenges of putting humanoid robots into space is developing cognitive capabilities for the robots with an interface that allows human astronauts to collaborate with the robots as naturally and efficiently as they would with other astronauts. In this joint effort with NASA and the entire Robonaut team we are integrating natural language and gesture understanding, spatial reasoning incorporating such features as human-robot perspective taking, and cognitive model-based understanding to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The first area, perspective taking, is focused on providing robots with the ability to reason about non-egocentric frames of reference in order to improve humanrobot collaboration, such as with NASA's Robonaut [3]. In a case study of astronaut extravehicular training, Trafton et al [4], found that over 85% of astronaut utterances involving spatial frames of reference were either object-centered, exocentric, addresseecentered, or deictic, as opposed to ego-centric.…”
Section: Related Workmentioning
confidence: 99%
“…The first area, perspective taking, is focused on providing robots with the ability to reason about non-egocentric frames of reference in order to improve humanrobot collaboration, such as with NASA's Robonaut [3]. In a case study of astronaut extravehicular training, Trafton et al [4], found that over 85% of astronaut utterances involving spatial frames of reference were either object-centered, exocentric, addresseecentered, or deictic, as opposed to ego-centric.…”
Section: Related Workmentioning
confidence: 99%
“…In collaboration with research at MIT, we work with a stationary robot, Leonardo 4 . Finally, in collaborative work with the Media Lab at MIT, the University of Massachusetts at Amherst, the University of Southern California at Los Angeles, Vanderbilt University, and NASA-Johnson Space Center, we use a humanoid robot, Robonaut 5,6 . Depending upon the platform and application, we are collaborating on interface and cognitive issues 7,8 in order to achieve easy interaction and facilitate cooperation and collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in works as [16,17], integration of natural language and gesture understanding was made in order to obtain a more natural interface in space and medical robotic applications. One of the most sophisticated and integrated systems can be found in [18].…”
Section: Related Workmentioning
confidence: 99%